De novo genome assembly of the partial homozygous dihaploid potato identified PVY resistance gene (Rychc) derived from Solanum chacoense - Akai, Kotaro (Breeding science, 2023)
Copyright © 2023 by JAPANESE SOCIETY OF BREEDING.